Factors Influencing Tourist Decision-Making Towards Traveling to Luang Prabang - Montira Maneesaeng มณฑิรา มณีแสง; William P. Wall วิลเลี่ยม พี วอลล์ (Dusit Thani College Journal, 2018)
The objectives of these study were 1) to analyze behavior factors (Psychology factors and Cultural and Social Factors) influencing tourist decision-making towards traveling to Luang Prabang; and 2) to analyze marketing mix factors influencing tourist decision-making towards traveling to Luang Prabang. Research Methodology: The sample consisted of 415 respondents. The sampling was quota sampling method to collect the sampling from 5 tourist attractions in Luang Prabang. The data was analyzed by frequency, percentage, mean, and standard deviation. The hypotheses were analyzed by and Multiple Regression Analysis. Research findings:1) Cultural and social factor has influencing with the tourist decision making towards traveling to Luang Prabang, and 2) Marketing mix factors has influencing with the tourist decision making towards traveling to Luang Prabang.